Fifteen-Year Retrospective Study: Prevalence of Bacterial Isolates in Mastitis-Suspected Milk Samples Submitted to Central Veterinary Laboratory, Nepal - Khanal, Shiva (Journal of the Institute of Agriculture and Animal Science, 2024)
Bovine mastitis, a prevalent mammary gland inflammation, significantly impacts dairy production worldwide. This study investigated the changing landscape of mastitis-causing bacteria in Nepal. A retrospective analysis of secondary data was conducted, utilizing technical bulletins published by the Central Veterinary Laboratory (CVL) in Kathmandu over a fifteen-year period (2003/2004 to 2017/2018). The analysis focused on 3,445 bovine milk samples screened for mastitis using the California Mastitis Test (CMT).The analysis revealed Staphylococcus spp. as the most prevalent bacterial isolate (2,948 positive samples), followed by E. coli and Streptococcus spp. This finding suggests a potential shift in the dominant mastitis pathogens in Nepal, with Staphylococcus spp. potentially surpassing E. coli compared to previous reports. These results highlight the importance of implementing hygiene practices during milking to reduce the spread of contagious pathogens like Staphylococcus spp. Additionally, maintaining clean milking environments can help minimize E. coli infections. Further research is warranted to understand the factors driving this potential shift in bacterial prevalence and develop targeted prevention and control strategies for mastitis in Nepal.